Cover. Issue 10 (12th October 2020) - Sung, Heejong; Hyland, Paula L.; Pemov, Alexander; Sabourin, Jeremy A.; Baldwin, Andrea M.; Bass, Sara; Teshome, Kedest; Luo, Wen; ,; Widemann, Brigitte C.; Stewart, Douglas R.; Wilson, Alexander F.
Abstract : The cover image is based on the Original Article Genome‐wide association study of café‐au‐lait macule number in neurofibromatosis type 1 by Alexander Pemov et al., https://doi.org/10.1002/mgg3.1400 .